PENGEMBANGAN LKPD INTERAKTIF MATERI PANTUN DENGAN BERBANTUAN APLIKASI QUIZIZZ KELAS V SDN PUCANG IV SIDOARJO - Ni'matul Mutammimah; Hari Satrijono; Fitria Kurniasih (Jurnal Muassis Pendidikan Dasar, 2022)
Interactive LKPD is a student worksheet that contain subject matter and computer- based questions. The purpose of this research was to know validty and efectivity of interactive LKPD through quizizz application. The type of this research is development study by Borg and Gall. The subject of this research were 48 students of 5th grade Pucang IV Sidoarjo elementary school. Data was collected by interview, questionnaris, and tests. Data analysis techinques were carried out with validty sheet, questionnaries and tests. The result of product validty is 87,8%, question validty is 85,4%, subject matter validty is 88,4%, questionnary get 99% percentage, and test get 85% percentage. Based on this results, we can know that development interactive LKPD through quizizz application is valid and effective to be applied in learning.